MAJOR THEORETICAL APPROACHES TO CONSTRUCTIVE CONFLICT RESOLUTION IN THE NORTH CAUCASUS - Popov, Maxim (Politologija, 2017)
This article explores the major approaches to the study of conflict resolution strategy from a variety of interdisciplinary perspectives. It argues that conflict resolution strategy, as a civil integration resource, is a necessary tool for overcoming deep-rooted ethnic conflicts in the unstable North Caucasus. This research pursues the goal of analyzing how the strength of civil integration can affect conflict resolution and peacebuilding. The author considers the essential factors of protracted ethnic conflicts and emphasizes the destabilizing role of the repoliticization of ethnicity in a crisis society. The concept of ethnic, “identity-based” conflicts is the heuristic theoretical model of exploring causes for increased ethnoreligious tensions in the North Caucasus. This article focuses on the ability of conflict resolution strategy to de-escalate growing tensions and transform protracted identity-based conflicts. The need to stimulate civil integration is caused by moral and structural causes: from the ethical point of view, the creation of an inclusive society is the fundamental societal goal; structural factors are related to the need to reduce inequalities and differences leading to social fragmentation and an escalation of ethnic conflicts. Among the structural conditions of regional conflicts, the author names ethnosocial inequalities, a civil identity crisis, ethnopolitical neo-authoritarianism, large-scale socioeconomic polarization and an “ideological combat” between secular modernization and religious fundamentalism. While discussing conflict resolution strategies, it is necessary to consider the following: 1) Peace and integration within the North Caucasus is a macropolitical project, the content of which is determined by issues of social cohesion and civil solidarity; 2) The development of the North Caucasus after the end of armed ethnic conflicts shows the inadmissibility of political demodernization, fundamentalism and isolationism. Today, the North Caucasus remains a crucially geopolitical macroregion, as it forms the southern volatile frontier of Russia. In this case, conflict resolution strategy must serve as an integrational and preventive tool on the conflict environment by way of providing structural solutions for deep-rooted cultural antagonisms, transforming and rationalizing ethnoregional contradictions.